Practical Virtual Use Method of CGI Program for User Creation Personal Portal Page Using DACS Web Service - Odagiri, Kazuya; Shimizu, Shogo; Ishii, Naohiro (Transactions on Engineering and Computing Sciences, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">A personal portal, which is an entrance wherein each user can acquire the information that s/he is interested in on a network, is often used as an alternative means of communication. However, there <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">were<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> a number of problems <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">in<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> the existing personal portals. For example, because the Web page as a personal portal <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">wa<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">s generated by the program located on the specific Web server which is managed by a system administrator, it <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">wa<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">s not always ideal for all users. To solve this kind of problems, we developed two Web Service functions, which are realized on the network by introducing the Destination Addressing Control System (DACS) Scheme. These two Web Service functions are as next. The first is the function to extract the data for each user from a database and display it on the Web browser. The second is the function to retrieve the data for each user from a document medium and display it on the Web browser. Through these Web Service functions, each user can easily create a customized personal portal that displays personal information. <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">Then<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">, the above two functions <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">were <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">extended to manage information not only for each user but also for each group of users and for all users, and the extended two functions<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US"> were<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: SimSun; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> integrated as a DACS Web Service. By using the DACS Web Service, each user can create and customize the Web page as a personal portal for practical usage in an individual organization. <span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">However, when the use of it in a real network is assumed, it is difficult to make the Web page as the personal portal with a complicated function by the present web page as the personal portal using DACS Web Service Therefore, in this study, functional extension is performed. To be concrete, we realize the method of using the Common Gateway Interface (CGI) program opened to Internet by a user unit, and improve the present Web page as the personal portal using DACS Web Service by the method.